Advances in natural language processing, intelligent informatics and smart technology : selected revised papers from the eleventh International Symposium on Natural Language Processing (SNLP-2016) and the first Workshop in Intelligent Informatics and Smart Technology, 10-12 February 2016, Phranakhon, Si Ayutthaya, Thailand /: selected revised papers from the eleventh International Symposium on Natural Language Processing (SNLP-2016) and the first Workshop in Intelligent Informatics and Smart Technology, 10-12 February 2016, Phranakhon, Si Ayutthaya, Thailand. ([2018]) - Unknown
No abstract available